Investigated the Role of Financial Innovation Dimensions in Achieving Financial Success Requirements in A Sample of Private Banks in The Kurdistan Region of Iraq - Sultan, Hikmet R.; Azab, Sami Sami (Humanities Journal of University of Zakho, 2017)
In the last two decades, the world witnessed many developments and changes, including: globalization, the progress of information technology, and innovation and knowledge-based economy. These changes imposed new challenges for business organizations and the private banks. So, how to increase their competitiveness and maintaining it and succeeding in it became the key challenges for these organizations due to these changes and advances. Based on the foregoing the current study investigated the role of financial innovation dimensions in achieving financial success requirements in a sample of private banks in the Kurdistan Region of Iraq. which calculated a number of statistical indicators that formed the basis for the presentation and discussion of the results. A number of research questions were specified for the problem of the study and they were as follows: Whether there is a correlation between financial innovation dimensions and requirements of financial success in the surveyed Almassa? The extent of the impact of the relationship between financial innovation and the requirements of the dimensions of financial success in the surveyed banks? The study reached a number of conclusions, most important of which were: The results of the analysis showed that there was a significant correlation between every dimension of financial innovation and financial success at the macro level in the surveyed banks. There was a significant effect of financial innovation on the overall financial success throughout the surveyed banks. There was discrepancy towards financial success variable according to the adoption of the dimensions of financial innovation among the surveyed banks in the provinces of Dohuk, and Erbil, whereas results showed that there was no such discrepancy among the surveyed banks in the province of Sulaymaniyah. The study gave a number of recommendations consistent with the findings of the current study, as well as proposed a set of future studies for researchers in the field.